Peirce’s more-than-human philosophy, its precursors, and its heirs - Nöth Winfried; Santaella Lucia (Cultural Science)
The paper discusses the more-than-human aspects of Charles S. Peirce’s semiotic philosophy, contextualizes it within the history of ideas (Aristotle, the Medievals, Montaigne, Descartes) and examines its syntony with and differences from 21st century trends of cultural and philosophical studies (posthumanism, nonhuman studies, Object-Oriented-Ontology, and the more-than-human paradigm).